Shipboard ADCP current measurements (600 kHz) during RV ALKOR cruise AL593 - Christian Winter; Robert Kopte; Marius Becker (PANGAEA, 2024)
Current velocities of the upper water column along the cruise track of R/V Alkor cruise AL593 were collected by a vessel-mounted 600 kHz RDI Workhorse ADCP. The ADCP transducer was located at 4.2 m below the water line. The instrument was operated in high-res., shallow water profiling mode (WM 12) with a bin size of 0.50 m, a blanking distance of 0.88 m, and a total of 90 bins, covering the depth range between 5.7 m and 50.2 m. Four consecutive pings were considered to form one ensemble average. Beam velocities as recorded by the data acquisition software WinRiver2 were transformed to ship coordinates and after merging with the navigation data from the ship extquotesingles gyro compass and Global Positioning systems into earth coordinates. Single-ping data were screened for bottom signals and, where appropriate, a bottom mask was manually processed. The ADCP was configured to measure bottom-track velocities, which were converted from beam to earth coordinates in the same manner as the water profile velocities. For each ping, the bottom-track velocity components were subtracted from the velocity profile to eliminate the ship movements and obtain true water velocities. The velocity data were averaged in time using an average interval of 60 s. Velocity quality flagging is based on different threshold criteria: Depth cells with ensemble-averaged percent-good values below 25% are marked as extquotesinglebad data extquotesingle. Depth cells with velocities above 1.0 m/s are flagged as extquotesinglebad data extquotesingle. Depth cells with a root-mean-square deviation between the measured ensemble-average velocity and a cell-wise running-mean velocity above 0.3 m/s are flagged as extquotesingleprobably bad data extquotesingle.